GIS and remote sensing based analysis for monitoring urban growth dynamics in Western Himalayan city of Dharamshala, India - Nishant Mehra; Janaki Ballav Swain (Urban Lifeline)
Abstract Ill-managed and unregulated urban sprawl has posed critical environmental and social challenges in the developing nations. There is an inherent need to monitor and measure the LULC changes to balance socio-economic development pressures and conservation measures. Integrating remote sensing and GIS has markedly helped frame intervention strategies in the fragile Himalayan regions. The research proposes establishing intervention strategies by monitoring LULC transitions occurring in Dharamshala, India, from 2016 to 2022. Maximum Likelihood Classification was performed on three Landsat 8 OLI images for 2016, 2019, and 2022 to prepare LULC thematic maps. The geographical and topographical complexities of the region necessitated the use of spectral vegetation indices, ancillary data, and the Strahler order algorithm to accurately represent LULC classes in the form of post-classification correction measures. The overall accuracy was found to be 88.06%, 87.02%, and 91.09% for the years 2016, 2019, and 2022. The study revealed a 140% increase in built-up areas from 2016 to 2022. The findings indicate increased developmental pressures in the 1500 m elevation and the progression of the urban sprawl towards higher altitudes, thereby increasing the risk of environmental degradation and posing a significant danger to the ecological susceptibility of the region. The tourism sector was a key factor driving LULC transitions in the area.